An EFL Teacher's Challenges in Teaching English for Elementary School Students in an Inclusive Education Context - Kayla Artamevia Putri; Ista Maharsi (Fakultas Ilmu Budaya, Universitas Brawijaya, 2024)
Compared to other countries, the development of inclusive education in Indonesia remains underdeveloped. EFL teachers teaching in inclusive classrooms, in particular, encounter complexity of problems in the field. This paper aims to explore how an EFL elementary school teacher faces challenges in teaching students with special needs. Data were collected from semi-structured interviews and analyzed using Braun and Clarks’ thematic analysis (2006). Results indicate that teachers need to adjust the running government curriculum to meet the students’ needs. Then, during the implementation of the curriculum shadow teachers play crucial roles as the classroom teachers have limited time and attention. The shadow teachers can focus on helping and facilitating the students with special needs. More importantly, creative teaching strategies that can engage and cater all students (both regular and students with special needs) are required.